Work in the brazilian judiciary: application of ergonomic concepts - Yparraguirre, Ivany Terezinha Rocha; Lima, Gilson Brito Alves; Zotes, Luís Perez; Oliveira, Valmir Martins de (Brazilian Journal of Operations & Production Management, 2025)
Goal: The management of the Brazilian Judiciary has been undergoing transformations with the digitalization and certification of its work processes, aimed at improving the quality of its services, including accessibility, relevance and transparency of information, simplicity of formalities and speed. In this context, ergonomic issues that arise are highlighted. Design / Methodology / Approach: This research opts for a case study based on the ergonomic work analysis (EWA) of an Organizational Unit (OU) of the Brazilian Judiciary. The focus of the study is on the challenges to the adaptive capacity of employees and managers, with an emphasis on the impact of the new management of the Brazilian judiciary. Results: The research identifies risks to workers' health and productivity due to the intensification of the workload and the breakdown of the boundaries between work and non-work time. In order to mitigate these risks, ergonomic interventions were proposed, concluding with the role of ergonomics as an auxiliary tool for the humanized management of the Brazilian Judiciary. Limitations of the investigation: The application of EWA in a judicial unit involves the subjectivity of the researcher in drawing up the instrument and <s>the</s> peculiarity of <s>the</s> profile of the sample used. Practical implications: These are related to advances in the identification of knowledge regarding the contribution of ergonomics to improving productivity and quality and guaranteeing the health and safety of judicial workers. Originality / Value: Among results of this research, the importance of issues concerning the areas of workers' health and safety stands out, contributing to the Organization's strategic plan in fulfilling its institutional and social functions.